Teaching Pelvic Anatomy Using Existing Medical School Resources: A Pilot Study. (October 2015) - Braun, Kelli; Edmondson, Anna; Martin, Carys; Ray, Chadburn; Evans, Lance
Abstract : BACKGROUND: Knowledge of female pelvic anatomy is essential to training in obstetrics and gynecology; however, much of this teaching is done informally throughout residency. Our goal was to evaluate if using existing resources (lectures and cadavers) from our associated medical school could improve resident knowledge and confidence in female pelvic anatomy. METHODS: Residents attended two consecutive 1 hour lectures traditionally given to first-year medical students, (female pelvis and perineum), conducted by two faculty in the department of Cellular Biology and Anatomy. Residents completed pretesting and posttesting on a 50-item test composed of 25 cadaver tags, using existing dissected cadavers, and 25 multiple choice questions related to female pelvic anatomy, derived from an existing medical student secure test bank; results were reported as total percent correct. Three weeks elapsed between pretesting and posttesting. Residents were also asked to assess their confidence in knowledge of pelvic anatomy and in identifying female pelvic structures, using a five-point Likert scale. RESULTS: All residents (n=16) participated. Mean pretest scores of 54.6%±11.6 increased 24% at posttest to 72%±9.1 ( P <.05). Mean resident confidence in knowledge of pelvic anatomy increased 44% from 1.64 to 2.92 ( P <.05), and mean confidence in identification of pelvic structures increased 33% from 2.21 to 3.28 ( P <.05). CONCLUSION: Our pilot study shows promise for using existing medical school resources to provide structured teaching of female pelvic anatomy to obstetrics and gynecology residents while increasing resident knowledge and confidence.